Contact damage investigation of CVD carbonitride hard coatings deposited on cemented carbides. (January 2020) - El Azhari, I.; García, J.; Soldera, F.; Suarez, S.; Jiménez-Piqué, E.; Mücklich, F.; Llanes, L.
Abstract: The evolution of damage induced as contact load is increased has been investigated on single- and multilayered coated cemented carbides by means of spherical indentation. The main objective of the study was to assess the effect of the intermediate wear-resistant carbonitride layer on the contact damage resistance of industrial milling (multilayered) inserts. This was approached by evaluating systems consisting of a single carbonitride layer of different chemical nature: novel Zr(C, N) and conventional Ti(C, N) chemical vapor deposition (CVD) coatings. Deformation and damage phenomena were characterized using a wide range of advanced techniques: confocal laser scanning microscopy, scanning electron microscopy, focused ion beam and X-ray synchrotron. Zr(C, N) coated systems are found to exhibit a higher mechanical integrity than Ti(C, N) counterparts. Main reasons behind are the relatively different thermal residual stresses generated during CVD cooling, as a result of the dissimilar coefficient of thermal expansion between the coating and the substrate, as well as the intrinsic cohesive strength of the studied coatings. Such different mechanical response was also discerned to affect the interaction between cracking and layer assemblage in multilayer coated specimens. It then supports the beneficial effect of using Zr(C, N) as the intermediate wear-resistant layer toward enhanced performance of industrial milling inserts. Highlights: Zr(C, N) coated systems exhibit higher mechanical integrity than Ti(C, N) ones. Contact damage depends on surface integrity and residual stresses of layers. Crack propagation path is intergranular for Ti(C, N) and mainly transgranular for Zr(C, N). Crack propagation path results agree with previous micro-compression experiments.